Oceanic response to changes in the WAIS and astronomical forcing during the MIS31 superinterglacial - F. Justino; D. Lindemann; F. Kucharski; A. Wilson; D. Bromwich; F. Stordal (Climate of the Past, 2017)
Marine Isotope Stage 31 (MIS31, between 1085 and 1055 ka) was characterized by higher extratropical air temperatures and a substantial recession of polar glaciers compared to today. Paleoreconstructions and model simulations have increased the understanding of the MIS31 interval, but questions remain regarding the role of the Atlantic and Pacific oceans in modifying the climate associated with the variations in Earth's orbital parameters. Multi-century coupled climate simulations, with the astronomical configuration of the MIS31 and modified West Antarctic Ice Sheet (WAIS) topography, show an increase in the thermohaline flux and northward oceanic heat transport (OHT) in the Pacific Ocean. These oceanic changes are driven by anomalous atmospheric circulation and increased surface salinity in concert with a stronger meridional overturning circulation (MOC). The intensified northward OHT is responsible for up to 85 % of the global OHT anomalies and contributes to the overall reduction in sea ice in the Northern Hemisphere (NH) due to Earth's astronomical configuration. The relative contributions of the Atlantic Ocean to global OHT and MOC anomalies are minor compared to those of the Pacific. However, sea ice changes are remarkable, highlighted by decreased (increased) cover in the Ross (Weddell) Sea but widespread reductions in sea ice across the NH.